2020
DOI: 10.1186/s13052-020-0772-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of preterm birth among mothers who gave birth in East Africa: systematic review and meta-analysis

Abstract: Background: Preterm birth (PTB) can be caused by different factors. The factors can be classified into different categories: socio demographic, obstetric, reproductive health, medical, behavioral and nutritional related. The objective of this review was identifying determinants of PTB among mothers who gave birth in East African countries. Methods: We have searched the following electronic bibliographic databases: PubMed, Google scholar, Cochrane library, AJOL (African journal online). Cross sectional, case co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 88 publications
13
33
0
2
Order By: Relevance
“…Similarly, the pooled result shows multiple pregnancies are more likely to be delivered preterm. The result is consistent with other reported studies [ 11 , 58 , 69 71 ]. This is due to overstretching of uterus might stimulate early labor.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, the pooled result shows multiple pregnancies are more likely to be delivered preterm. The result is consistent with other reported studies [ 11 , 58 , 69 71 ]. This is due to overstretching of uterus might stimulate early labor.…”
Section: Discussionsupporting
confidence: 94%
“…Our ndings revealed that the likelihood of PTB among mothers in the age group less than 20 years of age was eight times higher compared to the mother's age group of 20-30 years. This is consistent with a systematic review and meta-analysis conducted in East Africa (34). The study is also supported by studies done in Canada (35) and Ethiopia (22).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this study revealed that mothers who were exposed to chronic medical illness (HIV, anemia, chronic kidney disease, and cardiac disease) during pregnancy had 5-fold higher odds of PTB compared to those who were not exposed to any medical illness. This nding is supported by studies carried out in Jimma, Southwest Ethiopia(13), and Debremarkose, northwest Ethiopia (32), and a systematic review and meta-analysis of East Africa (34). This might be due to medical disorders during or before pregnancy affects the placenta and the membrane, in turn, reduces the placental ow of oxygen and nutrients to the developing fetus in utero, and, thus, increases the risk of preterm birth (39).…”
Section: Discussionmentioning
confidence: 84%
“…Numerous studies have assessed the relationship between season and adverse birth outcomes. [13][14][15][16][17][18][19][20][21] These studies have typically focused on the seasonality of preterm birth and birth weight, whereas fewer studies have examined the relationship between season and less common adverse birth outcomes like stillbirth. 22 Several small studies have been conducted in sub-Saharan Africa, where adverse birth outcomes may be more tightly linked to distinct rainy and dry seasons and related agricultural cycles, 16 18 20 21 and one meta-analysis of studies conducted in East Africa found an increased risk of preterm birth during the rainy season.…”
Section: Open Accessmentioning
confidence: 99%